Ethnobotany and Pharmacognosy of Qust/ Kut (Saussurea lappa, C. B. Clarke) with Special Reference of Unani Medicine - Ansari, Shabnam (Pharmacognosy Reviews)
Saussurea lappa, CB Clarke is the root of a perennial herb commonly grew in cold and humid areas such as North Asia- Kashmir, neighboring Himalaya regions, Garhwal etc. It has been used in the treatment of various disease ailments and conditions in Unani medicine with the name of ‘Qust/ Kut’. In Unani medicine, qust had been used as a drug of choice in diseases such as bronchial asthma (spasmolytic), liver diseases (as liver tonic, anti-inflammatory and analgesics), nervine and brain disorders (as tonic), painful conditions (as analgesics), weakness, low body immunity (as immune enhancer), etc. This paper uniquely presents the morphological features, temperament, chemical constituents, pharmacological actions, usage in diseases, dose, adverse effects with the reference of not only the ethnobotanical data and pharma cological studies but also with the reference of Unani literature in detail. Pharmacological actions and uses of qust in Unani medicine are searched in the light of available pharmacological, cell line and clinical studies to identify those action and uses which are left to be tested and substantiated.
Keywords: Qust; Saussurea; Costus; Saussurea lappa; Kut; Unani medicine; Ayush